Preparation method and application of composite electrode
By preparing the Li3Fe2(PO4)3/Fe2O3 composite electrode, the problem of low electron transfer efficiency of traditional iron-based materials was solved, realizing the resource utilization and high-efficiency catalytic performance of waste lithium iron phosphate batteries, and possessing good organic pollutant degradation capabilities.
Patent Information
- Application Number
- CN202610015075.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-07
- Publication Date
- 2026-03-20
AI Technical Summary
Traditional iron-based materials have low electron transfer efficiency in Fenton or electrocatalytic reactions, resulting in low catalyst efficiency. Furthermore, the Li3Fe2(PO4)3 in spent lithium iron phosphate batteries is not fully utilized, and existing technologies have failed to effectively improve its catalytic performance.
By preparing Li3Fe2(PO4)3/Fe2O3 composite electrodes from waste lithium iron phosphate battery cathode materials, and utilizing Li3Fe2(PO4)3 to provide stable ion transport channels and Fe2O3 to provide active sites, combined with discharge plasma sintering technology, the electron transfer capability is optimized, and a highly efficient catalyst is prepared.
The composite electrode achieves efficient degradation of organic pollutants in Fenton or electrocatalytic reactions, with a florfenicol removal rate of over 90% within 2 hours, and is easy to collect and reuse.
Smart Images

Figure CN121698441A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of resource utilization of waste lithium-ion batteries and electrocatalytic water treatment. More specifically, this invention relates to a method for preparing composite electrodes using waste lithium iron phosphate powder as raw material and its application in degrading pharmaceutical pollutant wastewater. Background Technology
[0002] Waste lithium iron phosphate batteries contain various toxic and harmful substances, including fluorinated electrolytes, but also rich in rare and valuable resources such as lithium, iron, and phosphorus. Therefore, they need to be recycled to reduce environmental harm and achieve resource recycling. Through screening, calcination, and discharge plasma sintering processes, they can be transformed into electrode materials with catalytic functions, achieving "waste-to-waste treatment."
[0003] Traditional iron-based materials such as iron oxide and zero-valent iron are affected by electron transport rate and Fe 2+ / Fe 3+ The limitations of recycling lead to low efficiency in the prepared catalysts. Although they possess abundant active sites, their electron transfer capabilities still need optimization to improve their catalytic performance in Fenton or electrocatalysis. However, the Li3Fe2(PO4)3 contained in the cathode of spent batteries has a NASICON-type structure that provides stable ion transport channels. This overcomes the low electron transfer efficiency of traditional iron-based materials such as iron oxide. The synergistic effect of both can more easily catalyze the oxidant to produce highly active substances for the rapid degradation of organic pollutants in Fenton or electrocatalytic reactions. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a composite electrode and its application.
[0005] According to one aspect of the present invention, a method for preparing a composite electrode is provided, comprising the following steps: S1. After discharging the battery by immersing it in sodium sulfate solution, the outer casing is mechanically disassembled to separate the positive electrode sheet containing lithium iron phosphate active material. The positive electrode sheet is then subjected to multi-stage crushing combined with magnetic separation and air separation to separate metal impurities and obtain positive electrode powder. S2. Place the positive electrode powder into a muffle furnace and pyrolyze it under nitrogen protection for 3-4 hours to decompose the binder while maintaining the integrity of the aluminum foil structure, and obtain the pyrolyzed material. S3. The pyrolysis material is subjected to ultrasonic vibration to separate the lithium iron phosphate powder from the aluminum foil, thereby obtaining crude lithium iron phosphate powder; S4. Immerse the crude lithium iron phosphate powder in dilute sulfuric acid to remove residual metal impurities, filter it, and then dry it in a vacuum drying oven for 1-2 hours to obtain high-purity dry lithium iron phosphate powder. S5. Weigh a certain amount of high-purity dry lithium iron phosphate powder, sieve it through a sieve and obtain sieved powder. Place the sieved powder in a muffle furnace and calcine it in air atmosphere for 6-8 hours. After natural cooling, obtain a mixed powder of Li3Fe2(PO4)3 and Fe2O3. S6. Place carbon paper in a graphite mold, weigh a certain amount of mixed powder of Li3Fe2(PO4)3 and Fe2O3 and place it on the carbon paper of the graphite mold, and then place the graphite mold into a spark plasma sintering furnace. S7. Turn on the cooling water tank, vacuum pump and discharge plasma sintering furnace in sequence. After the furnace reaches a vacuum state, set the parameters and perform discharge plasma sintering. S8. After sintering, the graphite mold is removed, the sintered electrode is demolded, and then sandblasted, and then soaked in anhydrous ethanol and ultrasonically removed to remove impurities and oil stains from the electrode surface, thus obtaining the composite electrode, namely the Li3Fe2(PO4)3 / Fe2O3 composite electrode.
[0006] In some embodiments, the sodium sulfate solution in step S1 has a mass-volume fraction of 5-10%, the separated metallic impurities are copper and aluminum, and the pyrolysis temperature in step S2 is 400-500℃ / min.
[0007] In some embodiments, the concentration of dilute sulfuric acid in step S4 is 1 mol / L, and the drying temperature of the vacuum drying oven is 50-60°C.
[0008] In some implementations, the sieve in step S5 is a 200-mesh sieve, the oscillating sieve time is 15 minutes, and the calcination temperature of the muffle furnace is 600-800℃.
[0009] In some embodiments, the amount of mixed powder of Li3Fe2(PO4)3 and Fe2O3 weighed in step S6 is 8-10g, and the inner diameter of the graphite mold is 30mm.
[0010] In some embodiments, the sintering parameters in step S7 are: heating rate of 50°C / min, sintering temperature of 900°C, holding time of 10min, and sintering pressure of 20MPa.
[0011] According to another aspect of the present invention, a composite electrode is provided, which is prepared by a method for preparing a composite electrode.
[0012] According to another aspect of the present invention, an application of a composite electrode in the degradation of organic pollutants in wastewater is provided.
[0013] According to a fourth aspect of the present invention, a method for degrading organic pollutants in water is provided, the method employing a composite electrode to degrade organic pollutants in water, comprising the following steps: (1) An aqueous solution containing organic pollutants of concentration C1 and catalyst of concentration C2 is added to a single-chamber electrolytic cell, with a composite electrode as the anode and a stainless steel plate as the cathode, and degradation is carried out after energizing. (2) Start timing after powering on, take 1 mL of reaction solution at different reaction times t, add methanol of amount M1 to terminate the degradation, and detect the remaining concentration of pollutants in the taken reaction solution by high performance liquid chromatography.
[0014] In some embodiments, the organic pollutant is florfenicol, the pollutant concentration C1 is 5-20 ppm, the catalyst is persulfate, the catalyst concentration C2 is 8-10 g / L, the reaction time t is 0-120 min, and the amount of methanol added M1 is 20-30 μL.
[0015] The beneficial effects of the present invention are: (1) The Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared by the present invention has excellent physicochemical properties, more concentrated pore structure, and high porosity and high reactivity; (2) The Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared by the present invention has good cycling performance and high feasibility for degrading organic pollutants such as florfenicol; (3) The composite electrode prepared by the present invention improves the electron transfer efficiency through Li3Fe2(PO4)3 and provides active sites through Fe2O3. The combined effect of the two makes the electrode practical in electrocatalytic degradation of pollutants. The removal rate of florfenicol pollutants in water can reach more than 90% within 2 hours. (4) The Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared by this invention is easier to collect and reuse compared with traditional metal powder catalyst materials. Attached Figure Description
[0016] Figure 1 The images shown are a comparison of the physical image and the electron microscope image of the composite electrode and its powder material of the present invention, wherein (a) is a physical image of the composite electrode, (b) is a physical image of the powder material, (c) is an electron microscope image of the composite electrode, and (d) is an electron microscope image of the powder material.
[0017] Figure 2 This is a comparison diagram of the florfenicol degradation effect of the Li3Fe2(PO4)3 / Fe2O3 composite electrode, the Li3Fe2(PO4)3 electrode, and the Fe2O3 electrode of the present invention.
[0018] Figure 3 The image shows the XRD characterization of the Li3Fe2(PO4)3 / Fe2O3 composite electrode of the present invention. Detailed Implementation
[0019] The present invention is further described in detail through specific implementation examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. After reading this invention, any modifications of the present invention in various equivalent forms by those skilled in the art fall within the scope defined by the appended claims. Unless otherwise specified, all raw materials and reagents of the present invention are commercially available.
[0020] Example 1
[0021] A method for preparing a composite electrode includes the following steps: S1. After discharging the battery by immersing it in a 10% sodium sulfate solution, the outer casing is mechanically disassembled to separate the positive electrode sheet containing lithium iron phosphate active material. The positive electrode sheet is then subjected to multi-stage crushing combined with magnetic separation and air separation to separate copper and aluminum metal impurities, thus obtaining positive electrode powder. S2. The positive electrode powder is placed in a muffle furnace and pyrolyzed at 500°C for 3 hours under nitrogen protection to decompose the binder while maintaining the integrity of the aluminum foil structure, thus obtaining the pyrolyzed material. S3. The pyrolysis material is subjected to ultrasonic vibration to separate the lithium iron phosphate powder from the aluminum foil, thereby obtaining crude lithium iron phosphate powder; S4. Immerse the crude lithium iron phosphate powder in 1 mol / L dilute sulfuric acid to remove residual metal impurities, filter it, and then dry it in a vacuum drying oven at 60℃ for 2 hours to obtain high-purity dry lithium iron phosphate powder. S5. Weigh 40g of high-purity, dry lithium iron phosphate powder, mechanically vibrate and sieve it through a 200-mesh sieve for 15 minutes to obtain sieved powder. Place the sieved powder in a muffle furnace and calcine it at 800℃ for 8 hours in air atmosphere. After natural cooling, a mixed powder of orange-red Li3Fe2(PO4)3 and Fe2O3 is obtained. See the image below for a physical picture of this mixed powder. Figure 1 (b); S6. Place carbon paper in a graphite mold with an inner diameter of 30 mm, weigh 8 g of mixed powder of Li3Fe2(PO4)3 and Fe2O3 and place it on the carbon paper of the graphite mold, and then place the graphite mold into a spark plasma sintering furnace. S7. Turn on the cooling water tank, vacuum pump and discharge plasma sintering furnace in sequence. After the furnace reaches a vacuum state, set the parameters as follows: heating rate of 50℃ / min, sintering temperature of 900℃, holding time of 10min, sintering pressure of 20MPa, and then carry out sintering. S8. After sintering, remove the graphite mold, demold the sintered electrode, and then perform sandblasting. Soak the electrode in anhydrous ethanol and sonicate for 5 minutes, repeating this process three times to remove impurities and oil from the electrode surface, obtaining the composite electrode, namely the Li3Fe2(PO4)3 / Fe2O3 composite electrode. See the physical example. Figure 1 (a).
[0022] The orange-red mixed powder of Li3Fe2(PO4)3 and Fe2O3 prepared in this embodiment was subjected to scanning electron microscopy. Specific scanning electron microscopy images can be found in [link to image]. Figure 1 (d).
[0023] The Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared in this embodiment was subjected to scanning electron microscopy. Specific scanning electron microscopy images are shown below. Figure 1 (c).
[0024] Example 2
[0025] A method for preparing a composite electrode includes the following steps: S1. After discharging the battery by immersing it in a 5% sodium sulfate solution, the outer casing is mechanically disassembled to separate the positive electrode sheet containing lithium iron phosphate active material. The positive electrode sheet is then subjected to multi-stage crushing combined with magnetic separation and air separation to separate copper and aluminum metal impurities, thus obtaining positive electrode powder. S2. The positive electrode powder is placed in a muffle furnace and pyrolyzed at 400°C for 4 hours under nitrogen protection to decompose the binder while maintaining the integrity of the aluminum foil structure, thus obtaining the pyrolyzed material. S3. The pyrolysis material is subjected to ultrasonic vibration to separate the lithium iron phosphate powder from the aluminum foil, thereby obtaining crude lithium iron phosphate powder; S4. Immerse the crude lithium iron phosphate powder in 1 mol / L dilute sulfuric acid to remove residual metal impurities, filter it, and then dry it in a vacuum drying oven at 50°C for 1 hour to obtain high-purity dry lithium iron phosphate powder. S5. Weigh 40g of high-purity dry lithium iron phosphate powder, mechanically vibrate and sieve it through a 200-mesh sieve for 15min to obtain sieved powder, place the sieved powder in a muffle furnace, calcine it at 600℃ for 6h in an air atmosphere, and after natural cooling, obtain orange-red mixed powder of Li3Fe2(PO4)3 and Fe2O3. S6. Place carbon paper in a graphite mold with an inner diameter of 30 mm, weigh 10 g of mixed powder of Li3Fe2(PO4)3 and Fe2O3 and place it on the carbon paper of the graphite mold, and then place the graphite mold into a spark plasma sintering furnace. S7. Turn on the cooling water tank, vacuum pump and discharge plasma sintering furnace in sequence. After the furnace reaches a vacuum state, set the parameters as follows: heating rate of 50℃ / min, sintering temperature of 900℃, holding time of 10min, sintering pressure of 20MPa, and then carry out sintering. S8. After sintering, remove the graphite mold, demold the sintered electrode, and then perform sandblasting. Soak the electrode in anhydrous ethanol and sonicate for 5 minutes, repeating twice to remove impurities and oil stains from the electrode surface, thus obtaining the composite electrode, namely the Li3Fe2(PO4)3 / Fe2O3 composite electrode.
[0026] Example 3
[0027] A method for preparing a composite electrode includes the following steps: S1. After discharging the battery by immersing it in a 7.5% sodium sulfate solution, the outer casing is mechanically disassembled to separate the positive electrode sheet containing lithium iron phosphate active material. The positive electrode sheet is then subjected to multi-stage crushing combined with magnetic separation and air separation to separate copper and aluminum metal impurities, thereby obtaining positive electrode powder. S2. The positive electrode powder is placed in a muffle furnace and pyrolyzed at 450°C for 3.5 hours under nitrogen protection to decompose the binder while maintaining the integrity of the aluminum foil structure, thus obtaining the pyrolyzed material. S3. The pyrolysis material is subjected to ultrasonic vibration to separate the lithium iron phosphate powder from the aluminum foil, thereby obtaining crude lithium iron phosphate powder; S4. Immerse the crude lithium iron phosphate powder in 1 mol / L dilute sulfuric acid to remove residual metal impurities, filter it, and then dry it in a vacuum drying oven at 55℃ for 1.5 h to obtain high-purity dry lithium iron phosphate powder. S5. Weigh 40g of high-purity dry lithium iron phosphate powder, mechanically vibrate and sieve it through a 200-mesh sieve for 15min to obtain sieved powder, place the sieved powder in a muffle furnace, calcine it at 700℃ for 7h in an air atmosphere, and after natural cooling, obtain orange-red mixed powder of Li3Fe2(PO4)3 and Fe2O3. S6. Place carbon paper in a graphite mold with an inner diameter of 30 mm, weigh 9 g of mixed powder of Li3Fe2(PO4)3 and Fe2O3 and place it on the carbon paper of the graphite mold, and then place the graphite mold into a spark plasma sintering furnace. S7. Turn on the cooling water tank, vacuum pump and discharge plasma sintering furnace in sequence. After the furnace reaches a vacuum state, set the parameters as follows: heating rate of 50℃ / min, sintering temperature of 900℃, holding time of 10min, sintering pressure of 20MPa, and then carry out sintering. S8. After sintering, remove the graphite mold, demold the sintered electrode, and then perform sandblasting. Soak the electrode in anhydrous ethanol and sonicate for 5 minutes, repeating 3 times to remove impurities and oil stains from the electrode surface, thus obtaining the composite electrode, namely the Li3Fe2(PO4)3 / Fe2O3 composite electrode.
[0028] Example 4
[0029] The Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared in Example 1 was characterized by XRD, and the specific results are shown in [the table below]. Figure 3 .
[0030] Figure 3The XRD patterns shown confirm a phase transition in lithium iron phosphate, and the XRD patterns are consistent with the reference structures of Li3Fe2(PO4)3 (ICSD number: 80-1515) and Fe2O3 (ICSD number: 79-0007). This phase transition process implies that LiFePO4 transforms into Li3Fe2(PO4)3 and Fe2O3 during muffle furnace calcination. Li3Fe2(PO4)3 is a monoclinic superionic conductor (space group P21 / n) with a significant (-121) diffraction peak at 2θ = 20.726° (lattice spacing = 4.28 Å). The monoclinic framework exhibits enhanced ion transport kinetics due to its extended interstitial vacancies, while the rigid PO4... 3- The tetrahedral network ensures the stability of the structure. The presence of Fe2O3 is attributed to the thermal decomposition of LiFePO4 under oxidizing conditions. Figure 3 This indicates that the Li3Fe2(PO4)3 / Fe2O3 composite electrode was successfully prepared by the spark plasma sintering method of this invention.
[0031] Example 5
[0032] A method for degrading organic pollutants in water, comprising the following steps: The method uses the Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared in Example 1 to degrade florfenicol in water. (1) An aqueous solution containing 10 ppm florfenicol and 1 ppm persulfate was added to a single-chamber electrolytic cell. A composite electrode was used as the anode and a stainless steel plate as the cathode. The current density was 10 mA / cm². 2 Degradation occurs under certain conditions; (2) After powering on, start timing. At 0, 5, 10, 20, 30, 45 and 60 min respectively, take 1 mL of reaction solution and add it to a 2 mL liquid chromatography vial. Add 20 μL of methanol to terminate the degradation. Detect the remaining concentration of florfenicol in the above-mentioned reaction solution by high performance liquid chromatography.
[0033] Example 5: Comparison of the degradation effects of Fe2O3 electrode, Li3Fe2(PO4)3 electrode and Li3Fe2(PO4)3 / Fe2O3 composite electrode on florfenicol
[0034] In this embodiment, Fe2O3 and Li3Fe2(PO4)3 electrodes were used instead of the composite electrode as the anode, respectively. Following the method in Example 4, the degradation effects of Fe2O3 and Li3Fe2(PO4)3 electrodes on florfenicol were detected and compared. Specific test results are shown below. Figure 2 .
[0035] Depend on Figure 2It can be seen that the Li3Fe2(PO4)3 / Fe2O3 composite electrode prepared in Example 1 of the present invention has a degradation rate of 100% for florfenicol at 60 min, which is significantly better than the degradation rate of florfenicol by the Fe2O3 electrode and the Li3Fe2(PO4)3 electrode. Therefore, the Li3Fe2(PO4)3 / Fe2O3 composite electrode of the present invention has superior degradation performance compared with the Fe2O3 electrode and the Li3Fe2(PO4)3 electrode.
[0036] The above descriptions are merely some embodiments of the present invention. For those skilled in the art, various modifications and improvements can be made without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite electrode, characterized in that, Includes the following steps: S1. After discharging the battery by immersing it in sodium sulfate solution, the outer casing is mechanically disassembled to separate the positive electrode sheet containing lithium iron phosphate active material. The positive electrode sheet is then subjected to multi-stage crushing combined with magnetic separation and air separation to separate metal impurities and obtain positive electrode powder. S2. The positive electrode powder is placed in a muffle furnace and pyrolyzed under nitrogen protection for 3-4 hours to decompose the binder while maintaining the integrity of the aluminum foil structure, thus obtaining the pyrolyzed material. S3. The pyrolysis material is subjected to ultrasonic vibration to separate the lithium iron phosphate powder from the aluminum foil, thereby obtaining crude lithium iron phosphate powder; S4. Immerse the crude lithium iron phosphate powder in dilute sulfuric acid to remove residual metal impurities, filter it, and then dry it in a vacuum drying oven for 1-2 hours to obtain high-purity dry lithium iron phosphate powder. S5. Weigh a certain amount of the high-purity dry lithium iron phosphate powder, sieve it through a sieve and obtain sieved powder, place the sieved powder in a muffle furnace and calcine it in air atmosphere for 6-8 hours, and after natural cooling, obtain a mixed powder of Li3Fe2(PO4)3 and Fe2O3. S6. Place carbon paper in a graphite mold, weigh a certain amount of the mixed powder of Li3Fe2(PO4)3 and Fe2O3 and place it on the carbon paper of the graphite mold, and then place the graphite mold in a spark plasma sintering furnace. S7. Turn on the cooling water tank, vacuum pump and discharge plasma sintering furnace in sequence. After the furnace reaches a vacuum state, set the sintering parameters and perform discharge plasma sintering. S8. After sintering, the graphite mold is removed, the sintered electrode is demolded, and then sandblasted, and then soaked in anhydrous ethanol and ultrasonically removed to remove impurities and oil stains from the electrode surface, thus obtaining a composite electrode, namely Li3Fe2(PO4)3 / Fe2O3 composite electrode.
2. The method for preparing a composite electrode according to claim 1, characterized in that, In step S1, the sodium sulfate solution has a mass-volume fraction of 5-10%, and the separated metallic impurities are copper and aluminum. In step S2, the pyrolysis temperature is 400-500℃ / min.
3. The method for preparing a composite electrode according to claim 1, characterized in that, In step S4, the concentration of dilute sulfuric acid is 1 mol / L, and the drying temperature of the vacuum drying oven is 50-60℃.
4. The method for preparing a composite electrode according to claim 1, characterized in that, In step S5, the sieve is a 200-mesh sieve, the duration of the vibrating sieve is 15 minutes, and the calcination temperature of the muffle furnace is 600-800℃.
5. The method for preparing a composite electrode according to claim 1, characterized in that, In step S6, the amount of mixed powder of Li3Fe2(PO4)3 and Fe2O3 weighed is 8-10g, and the inner diameter of the graphite mold is 30mm.
6. The method for preparing a composite electrode according to claim 1, characterized in that, The sintering parameters in step S7 are: heating rate of 50℃ / min, sintering temperature of 900℃, holding time of 10min, and sintering pressure of 20MPa.
7. A composite electrode, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
8. Application of a composite electrode in the degradation of organic pollutants in wastewater.
9. A method for degrading organic pollutants in water, characterized in that, The degradation of organic pollutants in water using a composite electrode as described in claim 7 includes the following steps: (1) An aqueous solution containing organic pollutants of concentration C1 and catalyst of concentration C2 is added to a single-chamber electrolytic cell, with a composite electrode as the anode and a stainless steel plate as the cathode, and degradation is carried out after energizing. (2) Start timing after powering on, take 1 mL of reaction solution at different reaction times t, add methanol of amount M1 to terminate the degradation, and detect the remaining concentration of pollutants in the taken reaction solution by high performance liquid chromatography.
10. A method for degrading organic pollutants in water according to claim 9, characterized in that, The organic pollutant is florfenicol, the pollutant concentration C1 is 5-20 ppm, the catalyst is persulfate, the catalyst concentration C2 is 8-10 g / L, the reaction time t is 0-120 min, and the amount of methanol added M1 is 20-30 μL.